Sources of image in the Nahjul Balaghah - Ahmad , Adnan; Omran, Montajab (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
مصادر الصّورة الفنّيّة في نهج البلاغة عدنان أحمد منتجب عمران يدرس البحث مصادر الصورة الفنية في نهج البلاغة , فيحاولُ الوقوفَ على منابعِها , وأسبابِ خروجها بالشكلِ الذي ظهرت فيه , ويبرز دورَ القرآن الكريم الجليَّ في رسمِ صورِ النهجِ الفنيّةِ , ويناقشُ قوةَ الآراءِ التي ترى في الانفتاحِ الثقافيِّ عاملاً رئيساً أو مصدراً بنيت عليه الصورةُ الفنيةُ في النهجِ أو وهنها . كما يظهر أثر كلٍّ من الأحاديث النّبويّة والأدب والبيئة المكانيّة والمجتمع في فكر الإمام عليّ (ع) , وبالتالي دورها في خلق الصورة الفنيّة في نهج البلاغة . The research looks at the Sources of image in the Nahjul Balaghah, then the research tries to stand up on it, and the reasons for its departure in the form in which it appeared. The research seeks to highlight the role of the Al Quran in drawing the artistic image in the approach. It discusses the power of opinions that see cultural openness as a major factor on which the image in the Nahjul Balaghah, or weakness. The research also shows the impact of prophetic traditions, literature, spatial environment and society in the thought of Imam Ali. and thus its role in creating its artistic image.